Impact of Stress Hyperglycemia on Early Neurological Deterioration in Acute Ischemic Stroke Patients Treated With Intravenous Thrombolysis - Wang, Ling; Cheng, Qiantao; Hu, Ting; Wang, Nuo; Wei, Xiu'e; Wu, Tao; Bi, Xiaoying (Frontiers in Neurology, 2022)
Background and Purpose It has been widely reported that stress hyperglycemia contributes to poor prognosis in patients experiencing acute ischemic stroke (AIS). However, its predictive value for early neurological deterioration (END) after intravenous administration of recombinant tissue-type plasminogen activator (IV-rtPA) in AIS patients is still unclear. The aim of this study was to evaluate the impact of stress hyperglycemia on the risk of END after IV-rtPA. Methods A total of 798 consecutive patients treated with IV-rtPA were included in this study. The stress hyperglycemia ratio (SHR) was calculated as fasting plasma glucose level at admission (mg/dl)/glycosylated hemoglobin (HbAlc) (%). END was defined as a National Institutes of Health Stroke Scale Score (NIHSS) ≥ 4 points 24 h after IV-rtPA, and poor functional outcome at discharge was defined as a modified Rankin Scale (mRS) score of 3–6 at discharge. Patients with a prior history of diabetes or HbAlc ≥ 6.5% were considered to have diabetes mellitus. Patients were grouped according to SHR values. Multivariate logistical regression was used to evaluate the risk of END for patients within specific SHR categories. Results In total, 139 (17.4%) patients had END. After adjusting for confounders, the highest tertile group had higher risks of END and poor functional outcome at discharge than those of patients in the lowest tertile group (OR, 1.95; 95% CI, 1.21–3.15; p = 0.006) (OR, 1.85; 95% CI, 1.163–2.941; p = 0.009), and the predictive value of high SHR for END was also significant in patients with diabetes mellitus (OR, 3.05; 95% CI, 1.29–7.21; p = 0.011). However, a significant association of high SHR and poor functional outcome was only found in patients without diabetes (OR, 1.85; 95% CI, 1.002–3.399; p = 0.045). Conclusion A higher SHR predicted that patients with severe stress hyperglycemia had higher risks of END and poor functional outcome at discharge after IV-rtPA.